Building Language Literacy and Moral Values: Evaluation of the Use of Mother Tongue in Religious Education Learning - Astawa, Nyoman Temon; Sueca, Nyoman; Nerawati, Ni Gusti Ayu Agung; Deng, Jianbang (Universitas Negeri Makassar, 2025)
This study aims to evaluate the implementation of Religious Education in elementary schools using the mother tongue as the primary medium of instruction. The study is motivated by the low internalization of moral values among students, despite religious lessons being conducted routinely. The mother tongue was chosen as the approach because it is considered closer to students’ daily lives and capable of fostering a stronger emotional connection to religious content. The research employed a descriptive qualitative method involving classroom observations, interviews with teachers and students, and analysis of learning documents. The results indicate that the use of the mother tongue in Religious Education can enhance students’ understanding of religious concepts, promote their engagement in spiritual discussions, and reinforce daily worship practices. However, several challenges emerged, including limited religious vocabulary in local languages and the need for teacher training. The study recommends systematically integrating the mother tongue into religious instruction at the elementary level to cultivate moral values in a contextual and meaningful way.